Chronic obstructive pulmonary disease and glucose metabolism: a bitter sweet symphony - Mirrakhimov, Aibek E (BioMed Central, 2012)
Chronic obstructive pulmonary disease, metabolic syndrome and diabetes mellitus are common and underdiagnosed medical conditions. It was predicted that chronic obstructive pulmonary disease will be the third leading cause of death worldwide by 2020. The healthcare burden of this disease is even greater if we consider the significant impact of chronic obstructive pulmonary disease on the cardiovascular morbidity and mortality. Chronic obstructive pulmonary disease may be considered as a novel risk factor for new onset type 2 diabetes mellitus via multiple pathophysiological alterations such as: inflammation and oxidative stress, insulin resistance, weight gain and alterations in metabolism of adipokines. On the other hand, diabetes may act as an independent factor, negatively affecting pulmonary structure and function. Diabetes is associated with an increased risk of pulmonary infections, disease exacerbations and worsened COPD outcomes. On the top of that, coexistent OSA may increase the risk for type 2 DM in some individuals. The current scientific data necessitate a greater outlook on chronic obstructive pulmonary disease and chronic obstructive pulmonary disease may be viewed as a risk factor for the new onset type 2 diabetes mellitus. Conversely, both types of diabetes mellitus should be viewed as strong contributing factors for the development of obstructive lung disease. Such approach can potentially improve the outcomes and medical control for both conditions, and, thus, decrease the healthcare burden of these major medical problems.